Learner Autonomy among Master 1 EFL Students in Google Meet–Based Online Learning Environments - Meguimi Amira (My University, 2026)
Abstract The landscape of higher education has witnessed a significant shift towards digital environments, particularly in English as a Foreign Language (EFL) contexts. This transition has placed a high demand on learner autonomy, as students are required to manage their learning with limited teacher supervision. This study investigates the level of learner autonomy among Master 1 EFL students at Mohamed Chérif Messaadia University (Souk Ahras) within Google Meet-based online learning environments. Specifically, it explores students' independent learning practices and identifies the pedagogical and technical challenges that hinder their autonomy.To achieve these objectives, the study adopted a quantitative research design. A questionnaire was administered to a sample of 24 Master 1 EFL students to collect data regarding their goal-setting habits, use of digital tools, and perceptions of online independence. The results revealed that while students demonstrate a moderate level of autonomy—evidenced by their engagement in independent study and goal-setting—they still face significant obstacles. The findings highlight lack of motivation, technical issues, and weak time management as the primary challenges. The study concludes that while Google Meet provides a platform for independence, developing full autonomy is a gradual process that requires explicit strategy training and structured teacher support. -------------------- ﻣﻠﺨ ﺺﺗﮭﺪف ھﺬه اﻟﺪراﺳﺔ إﻟﻰ اﺳﺘﻜﺸﺎف اﺳﺘﻘﻼﻟﯿﺔ اﻟﻤﺘﻌﻠﻢ ﻟﺪى طﻠﺒﺔ اﻟﺴﻨﺔ اﻷوﻟﻰ ﻣﺎﺳﺘﺮ ﺗﺨﺼﺺ اﻟﻠﻐﺔ اﻹﻧﺠﻠﯿﺰﯾﺔ Google ﻣﺴﺎﻋﺪﯾﺔ ﺑﺴﻮق أھﺮاس ﻓﻲ ﺑﯿﺌﺎت اﻟﺘﻌﻠﻢ اﻹﻟﻜﺘﺮوﻧﻲ اﻟﻤﻌﺘﻤﺪة ﻋﻠﻰ ﻣﻨﺼﺔ ﺑﺠﺎﻣﻌﺔ ﻣﺤﻤﺪ اﻟﺸﺮﯾﻒ Meet ﻛﻤﺎ ﺗﺴﻌﻰ إﻟﻰ اﻟﺘﻌﺮف ﻋﻠﻰ ﻣﻤﺎرﺳﺎت اﻟﺘﻌﻠﻢ اﻟﺬاﺗﻲ واﻟﺼﻌﻮﺑﺎت اﻟﺒﯿﺪاﻏﻮﺟﯿﺔ واﻟﺘﻘﻨﯿﺔ اﻟﺘﻲ ﺗﺆﺛﺮ 24 ﻣﻦ اﻋﺘﻤﺪت اﻟﺪراﺳﺔ ﻋﻠﻰ اﻟﻤﻨﮭﺞ اﻟﻜﻤﻲ ﺑﺎﺳﺘﺨﺪام اﺳﺘﺒﯿﺎن وُزّع ﻋﻠﻰ ﻋﯿﻨﺔ ﻣﻜﻮﻧﺔ ﻋﻠﻰ اﺳﺘﻘﻼﻟﯿﺔ اﻟﻄﻠﺒﺔ. . وﺗﻢ ﺟﻤﻊ اﻟﺒﯿﺎﻧﺎت ﺣﻮل ﺗﺤﺪﯾﺪ اﻷھﺪاف اﻟﺘﻌﻠﯿﻤﯿﺔ، واﺳﺘﺨﺪام اﻷدوات اﻟﺮﻗﻤﯿﺔ، 1 طﺎﻟﺒًﺎ ﻣﻦ طﻠﺒﺔ ﻣﺎﺳﺘﺮ أظﮭﺮت اﻟﻨﺘﺎﺋﺞ أن اﻟﻄﻠﺒﺔ ﯾﺘﻤﺘﻌﻮن ﺑﻤﺴﺘﻮى ﻣﺘﻮﺳﻂ وﺗﺼﻮرات اﻟﻄﻠﺒﺔ ﺣﻮل اﻟﺘﻌﻠﻢ اﻟﻤﺴﺘﻘﻞ ﻋﺒﺮ اﻹﻧﺘﺮﻧﺖ. ھﺪاف اﻟﺘﻌﻠﯿﻤﯿﺔ. وﻣﻊ ذﻟﻚ، واﺟﮫ اﻟﻄﻠﺒﺔ ﻋﺪة ﻣﻦ اﻻﺳﺘﻘﻼﻟﯿﺔ، وﯾﺘﺠﻠﻰ ذﻟﻚ ﻣﻦ ﺧﻼل اﻟﺘﻌﻠﻢ اﻟﺬاﺗﻲ وﺗﺤﺪﯾﺪ اﻷ ﺻﻌﻮﺑﺎت، ﻣﻦ ﺑﯿﻨﮭﺎ ﺿﻌﻒ اﻟﺪاﻓﻌﯿﺔ، واﻟﻤﺸﻜﻼت اﻟﺘﻘﻨﯿﺔ، وﺻﻌﻮﺑﺔ إدارة اﻟﻮﻗﺖ. وﺧﻠﺼﺖ اﻟﺪراﺳﺔ إﻟﻰ أن ﻤﻜﻦ أن ﺗﺪﻋﻢ اﻟﺘﻌﻠﻢ اﻟﻤﺴﺘﻘﻞ، إﻻ أن ﺗﻄﻮﯾﺮ اﺳﺘﻘﻼﻟﯿﺔ ﻛﺎﻣﻠﺔ ﯾﺘﻄﻠﺐ ﺗﻮﺟﯿﮭً ﺎ ﯾ Google Meet ﻣﻨﺼﺔ . ﺑﯿﺪاﻏﻮﺟﯿًﺎ واﺳﺘﺮاﺗﯿجيا -------------------- Résumé Cette étude examine l’autonomie des apprenants auprès des étudiants de Master 1 EFL à l’Université Mohamed Chérif Messaadia de Souk Ahras dans des environnements d’apprentissage en ligne basés sur Google Meet. Elle vise à explorer les pratiques d’apprentissage autonome des étudiants ainsi que les difficultés pédagogiques et techniques qui influencent leur autonomie. Afin d’atteindre ces objectifs, une approche quantitative a été adoptée à travers un questionnaire administré à un échantillon de 24 étudiants de Master 1 EFL. Les données recueillies portent sur la fixation des objectifs, l’utilisation des outils numériques et les perceptions des étudiants concernant l’apprentissage autonome en ligne. Les résultats montrent que les étudiants présentent un niveau modéré d’autonomie, notamment à travers l’apprentissage indépendant et la fixation d’objectifs. Cependant, plusieurs obstacles persistent, tels que le manque de motivation, les problèmes techniques et les difficultés de gestion du temps. L’étude conclut que Google Meet peut favoriser l’apprentissage autonome, mais que le développement d’une autonomie complète nécessite un accompagnement pédagogique et des stratégies d’apprentissage appropriées.
Keywords: Learner Autonomy; Online Learning; Google Meet; EFL Students; ﯿﺰﯾﺔ Google Meet ا; Autonomie de l’apprenant; apprentissage en ligne; étudiants EFL.